Repair of a Divergent Elbow Dislocation with Distal Ulnar Fracture in a Dog Using TightRope and External Skeletal Fixation - Garcia, Marcos; Bismuth, Camille; Deroy-Bordenave, Claire (VCOT Open, 2021)
The aim of this study was to report the outcome in a 6-year-old male English Setter dog that suffered a combination of divergent elbow dislocation and open distal ulnar fracture. This study is a case report. After surgical reduction in the elbow luxation, the dog was treated with the TightRope fixation system used as replacement of the lateral collateral ligament, a radioulnar positional screw, and external skeletal fixation. Removal of all implants was performed 3 months postoperatively. The 6-month follow-up visit found the dog without lameness, displaying normal activity, and with normal elbow range of motion and normal Campbell's test. Successful surgical management was achieved with good long-term results using TightRope, a positional screw, and an external skeletal fixator.
Keywords: dog; elbow luxation; divergent dislocation; TightRope; Monteggia injury